The Market Potential of Madura Stalls and The Socio-Economic Impact on Local Communities: A Community-Based Islamic Business Study - Ach Alfan Irhamsyah; Fahrurrozi (Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo, 2024)
Madurese are famous for their nomadic culture and trading skills, with Madurese warungs scattered across Indonesia's major cities. These stalls thrive with small capital thanks to perseverance, solid community networks, and high work ethic. This research explores the potential and social impact of Madurese warungs with a community-based Islamic business perspective, using qualitative methods with purposive and snowball sampling, as well as interviews, observations, and discussions. The results show that the success of Madura warungs depends on the quality of goods, good service, competitive prices, and 24-hour operations. In addition to economic impact, these stalls also increase social interaction, strengthen community ties, and promote inter-ethnic harmony. The findings show that Madurese warung not only contribute to the economy but also strengthen community networks. The research identifies policies to increase positive impacts and address challenges, such as business management training for MSMEs and cooperation with local governments. Thus, Madura warungs can continue to grow and provide greater benefits to local people and the Madura community.